A Degradable and Self-Healable Vitrimer Based on Non-isocyanate Polyurethane - Wu, Haitao; Jin, Biqiang; Wang, Hao; Wu, Wenqiang; Cao, Zhenxing; Wu, Jinrong; Huang, Guangsu (Frontiers in Chemistry, 2020)
Developing degradable and self-healable elastomers composed of reusable resources is of great value, but is rarely reported due to the undegradable molecular chains. Herein, we report a class of degradable and self-healable vitrimers based on non-isocyanate polyurethane elastomer. Such vitrimers are fabricated by copolymerizing bis(6-membered cyclic carbonate) and amino-terminated liquid nitrile rubber (ATBN). The networks topologies can rearrange by transcarbonation exchange reactions between hydroxyl and carbonate groups at elevated temperatures; as such vitrimers after reprocessing can recover 82.9-95.6 % of initial tensile strength and 59−131 % of initial storage modulus. Interestingly, the networks can be hydrolyzed and decarbonated in the strong acid solution to recover 75 % of the pure di(trimethylolpropane) monomer. Additionally, the elastomer exhibits excellent self-healing efficiency (~88 %) and fracture strain (~1200 %) by tuning the monomer feeding ratio. Therefore, this work provides a novel strategy to fabricate the sustainable elastomers with minimum environmental impact.